PENYULUHAN BAHAYA SEDENTARY LIFESTYLE PADA MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS KADIRI - Etika , Arif Nurma; Agnes, Yeni Lufiana Novita; Sulistyawati, Wiwin; Suharto, Idola Perdana Sulistyoning; Jayani, Indah; Susmiati, Susmiati; Nurseskasatmata, Satria Eureka; Ramayanti, Eva Dwi; Lutfi, Erik Irham; Yunalia, Endang Mei (Jurnal Abdi Masyarakat, 2023)
A Sedentary lifestyle is a low energy expenditure, which expends calories 1.5 METs or less. It most likely leads to various metabolic diseases, such as Diabetic Mellitus. Some factors influencing a sedentary lifestyle are knowledge, attitudes, gender, convenience, transportation, technological advances, COVID-19 outbreaks, and consequences. A sedentary behavior becomes a typical lifestyle among teenagers, including students. Therefore, counseling about a sedentary lifestyle and its effects is very much needed among students. This counseling aims to increase knowledge about the sedentary lifestyle and its dangers so that students can avoid it and increase physical activity. The implementation method in this counseling consists of 3 stages, these stages are preparation, implementation and evaluation. Sixty-five nursing students attended this counseling activity; most participants (70%) were female. The result shows that some respondents did not know about the sedentary lifestyle and its dangers. After counseling, almost all respondents knew about the sedentary lifestyle and its risks. Moreover, they were committed to reducing sedentary behavior and increasing physical activity. Based on the results, it can be concluded that counseling may increase students’ commitment to physical activity and sports.   Keywords: physical activity, Sedentary lifestyle